Fluconazole as a safe and effective alternative to ketoconazole in controlling hypercortisolism of recurrent Cushing’s disease: a case report - Chai, Shu Teng; Haydar Ali Tajuddin, Amalina; Abdul Wahab, Norasyikin; Mustafa, Norlaila; Sukor, Norlela; Kamaruddin, Nor Azmi (Kowsarmedical, 2018)
Introduction: Ketoconazole has long been the first-line medical therapy for controlling hypercortisolism secondary to either pituitary or adrenal pathology. However, it is largely unavailable in most countries. As a result, we have turned to fluconazole as a viable alternative in view of its favourable safety profile. Case Presentation: A 50-year-old lady developed recurrent Cushing’s disease after being in remission following transsphenoidal surgery (TSS) for a left pituitary microadenoma 16 years ago. The repeat MRI showed a right pituitary microadenoma (1.7 mm 1.3 mm) for which she underwent a second TSS. However, she continued to have persistent hypercortisolism despite repeated MRIs showing absence of tumour recurrence. She refused bilateral adrenalectomy and external radiotherapy. Ketoconazole was commenced at 200 mg twice daily for disease control but this was hindered by intolerable side effects including pruritus and skin exfoliation. In the meantime, she suffered a right hypertensive basal ganglia hemorrhage. Treatment was subsequently switched to cabergoline and the dose titrated to 0.5 mg daily. Fluconazole 400 mg daily was later added to control the persistent disease. Her clinical and biochemical parameters improved markedly three months after the addition of fluconazole. No adverse event was reported. Her disease has remained stable for the last 15 months up until the time of the recent clinic review. Conclusions: This case demonstrates the long-term efficacy of fluconazole in tandem with cabergoline for the control of recurrent Cushing’s disease.